UVB-Induced Microvesicle Particle Release and Its Effects on the Cutaneous Microenvironment - Frommeyer, Timothy C.; Gilbert, Michael M.; Brittain, Garrett V.; Wu, Tongfan; Nguyen, Trang Q.; Rohan, Craig A.; Travers, Jeffrey B. (Frontiers in Immunology, 2022)
Ultraviolet B radiation (UVB) has profound effects on human skin that results in a broad spectrum of immunological local and systemic responses and is the major cause of skin carcinogenesis. One important area of study in photobiology is how UVB is translated into effector signals. As the skin is exposed to UVB light, subcellular microvesicle particles (MVP), a subtype of bioactive extracellular vesicles, are released causing a variety of local and systemic immunological effects. In this review, we highlight keratinocyte MVP release in keratinocytes in response to UVB. Specifically, Platelet-activating factor receptor agonists generated by UVB result in MVP released from keratinocytes. The downstream effects of MVP release include the ability of these subcellular particles to transport agents including the glycerophosphocholine-derived lipid mediator Platelet-activating factor (PAF). Moreover, even though UVB is only absorbed in the epidermis, it appears that PAF release from MVPs also mediates systemic immunosuppression enhances tumor growth and metastasis. Tumor cells expressing PAF receptors can use this mechanism to evade chemotherapy responses, leading to treatment resistance for advanced cancers such as melanoma. Furthermore, novel pharmacological agents provide greater insight into the UVB-induced immune response pathway and a potential target for pharmacological intervention. This review outlines the need to more clearly elucidate the mechanism linking UVB-irradiation with the cutaneous immune response and its pathological manifestations. An improved understanding of this process can result in new insights and treatment strategies for UVB-related disorders from carcinogenesis to photosensitivity.